How COVID-19 pandemic period influences on the selected mental health parameters of Polish respondents? - Florek, Szymon; Piegza, Magdalena; Dębski, Paweł; Gorczyca, Piotr; Pudlo, Robert (Frontiers in Psychology, 2023)
Introduction There are many different articles about COVID-19 pandemic period and its influence on people and their behavior. Nevertheless, there is little research on the slightly later period of the pandemic, that is, the time when specific adaptation mechanisms in society should start to take place. Methods Our research was conducted by means of an online survey. Four hundred and eighty five adults participated, including 349 (71.96%) women and 136 (28.04%) men. The Buss-Perry aggression scale, Alcohol Use Disorders Identification Test and Generalized Anxiety Disorder 7 scale were used. The results were statistically processed using Statistica 13.3 software. Results Within the study population, positive correlations were noted between anxiety and generalized aggression, anger, hostility, physical and psychological aggression. In the female group, anxiety correlates positively with generalized aggression, anger, hostility, verbal and physical aggression. Among male subjects, anxiety correlates positively with aggression, anger, and hostility. Alcohol consumption has a significant association with verbal aggression. Statistically, more women experience anxiety, more men have inflated scores on the AUDIT scale and on verbal and physical aggression. Younger people are more likely than older people to experience anxiety and have inflated scores on hostility. Those with secondary education scored significantly higher on the GAD-7 scale and the aggression scale (and all subscales except anger) compared to respondents with higher education. Discussion As a result of adaptation to the COVID-19 pandemic, anxiety is no longer a factor in increased evels of alcohol consumption. The pandemic has not affected differences in alcohol consumption between men and women. The presence of a positive correlation between anxiety and aggression and the sociodemographic structure of those characterized by increased aggression are also unchanged. Anxiety directly influences aggressive behavior in a relatively strong way. Appropriate health-promoting measures should be implemented to protect the public from the negative effects of the COVID-19 pandemic.